If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7x + -3) + -1(6x + -5) + 9 = -5(x + -1) + -1(11x + 6) + 3 Reorder the terms: -1(-3 + 7x) + -1(6x + -5) + 9 = -5(x + -1) + -1(11x + 6) + 3 (-3 * -1 + 7x * -1) + -1(6x + -5) + 9 = -5(x + -1) + -1(11x + 6) + 3 (3 + -7x) + -1(6x + -5) + 9 = -5(x + -1) + -1(11x + 6) + 3 Reorder the terms: 3 + -7x + -1(-5 + 6x) + 9 = -5(x + -1) + -1(11x + 6) + 3 3 + -7x + (-5 * -1 + 6x * -1) + 9 = -5(x + -1) + -1(11x + 6) + 3 3 + -7x + (5 + -6x) + 9 = -5(x + -1) + -1(11x + 6) + 3 Reorder the terms: 3 + 5 + 9 + -7x + -6x = -5(x + -1) + -1(11x + 6) + 3 Combine like terms: 3 + 5 = 8 8 + 9 + -7x + -6x = -5(x + -1) + -1(11x + 6) + 3 Combine like terms: 8 + 9 = 17 17 + -7x + -6x = -5(x + -1) + -1(11x + 6) + 3 Combine like terms: -7x + -6x = -13x 17 + -13x = -5(x + -1) + -1(11x + 6) + 3 Reorder the terms: 17 + -13x = -5(-1 + x) + -1(11x + 6) + 3 17 + -13x = (-1 * -5 + x * -5) + -1(11x + 6) + 3 17 + -13x = (5 + -5x) + -1(11x + 6) + 3 Reorder the terms: 17 + -13x = 5 + -5x + -1(6 + 11x) + 3 17 + -13x = 5 + -5x + (6 * -1 + 11x * -1) + 3 17 + -13x = 5 + -5x + (-6 + -11x) + 3 Reorder the terms: 17 + -13x = 5 + -6 + 3 + -5x + -11x Combine like terms: 5 + -6 = -1 17 + -13x = -1 + 3 + -5x + -11x Combine like terms: -1 + 3 = 2 17 + -13x = 2 + -5x + -11x Combine like terms: -5x + -11x = -16x 17 + -13x = 2 + -16x Solving 17 + -13x = 2 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 17 + -13x + 16x = 2 + -16x + 16x Combine like terms: -13x + 16x = 3x 17 + 3x = 2 + -16x + 16x Combine like terms: -16x + 16x = 0 17 + 3x = 2 + 0 17 + 3x = 2 Add '-17' to each side of the equation. 17 + -17 + 3x = 2 + -17 Combine like terms: 17 + -17 = 0 0 + 3x = 2 + -17 3x = 2 + -17 Combine like terms: 2 + -17 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| 22x^2=-11x | | 0.25-3.4/0.2(1.6) | | 7x+5x+2y+20+90=360 | | 15/8=x/3 | | 3x+4x=3+4 | | A*a-b=55 | | =88.7-2.2(0.49+19.2) | | ax+b=2x^2-1 | | -4k= | | 88.7-2.2(0.49+19.2)= | | 11x/3-6==5 | | S=5m+5vform | | 5r+6-21=7r-10 | | 2-(3x+3)=7-5x | | 6(1x+9)=54 | | 19.85(12.5xt)=2.6-t | | e^4x=500 | | 3(-8+x)=6 | | (8x-4)(6x+2)=0 | | (7x+5y)-(4x-2y)= | | 5(s-3)=19 | | -7(7x+8)=-399 | | 3X^2-2y^2+4y-26=0 | | 6+6cosine(6x)=0 | | -2(2s-5)-10=-3(3s+1)-3 | | 6+6cos(6x)=0 | | 7-2d=11 | | 1/3x-9=-15 | | (2-9i)/(2-I) | | 11x-4=7x+40 | | 11(3p-4)+2= | | 8p^2=-96+64p |